Biological stimulation sand stabilization and dust prevention method

By spraying biostimulant liquid and cementing liquid containing yeast extract on the surface of the desert soil to form a crust, the problem of wind erosion of the desert soil caused by sandstorms is solved, and the effect of improving the load-bearing and wind-erosion resistance of the soil layer is achieved, while avoiding environmental pollution.

CN119331629APending Publication Date: 2025-01-21喀什大学
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411577556.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Frequent sandstorms in desert areas cause surface desert soil layers to be susceptible to wind erosion. Existing dust prevention methods are often environmentally polluted or costly.

Method used

Using biostimulation sand fixation and dust prevention methods, a stimulating liquid and cementing liquid containing yeast extract, ammonia chloride, sodium acetate, urea and calcium chloride are prepared and sprayed on the surface of the desert soil respectively to form a crust and improve the soil quality. Bearing capacity and resistance to wind erosion.

Benefits of technology

This method significantly improves the load-bearing capacity and wind erosion resistance of the surface layer of desert soil, increases the calcium content and strength of the soil, and has no risk of environmental pollution. It is suitable for areas such as the Taklimakan Desert.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The biological stimulation sand stabilization and dust prevention method comprises the steps that stimulation liquid and cementing liquid are applied to the surface layer of desert soil in sequence, the stimulation liquid contains yeast extract, ammonium chloride, sodium acetate and urea, and the cementing liquid further contains calcium chloride. Specific biological stimulation and cementing means are combined, crust is formed on the surface layer of the desert soil, and the bearing capacity and the wind erosion resistance of the surface layer of the desert soil are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention generally relates to a sand fixation and dust prevention method for desert areas. Background Art

[0002] Kashgar is located in the westernmost region of China, with an arid climate, low rainfall, and frequent sandstorms, which pose a major threat to the livelihoods and economic activities of local residents. It is imperative to reduce or even completely eliminate the hazards associated with sandstorms. One potential solution to this problem is to stabilize the surface desert soil layer, thereby reducing wind erosion. However, traditional methods of preventing desert soil erosion, including physical, chemical, and the use of plants and grass blocks, often lead to secondary environmental pollution or incur high costs. Summary of the invention

[0003] The object of the present invention is to provide a sand fixation and dust prevention method, which can reinforce the desert soil surface in a reliable and environmentally friendly manner.

[0004] According to the present invention, a method for biostimulation of sand fixation and dust prevention for the surface layer of desert soil is provided, comprising:

[0005] Prepare a stimulation solution, the composition of which is: yeast extract 0.08-0.12 g / L; ammonium chloride 11-14 mM; sodium acetate 40-45 mM; urea 300-400 mM; the balance is water;

[0006] Prepare a binder solution, the composition of which is: yeast extract 0.08-0.12 g / L; ammonium chloride 11-14 mM; sodium acetate 40-45 mM; urea 300-400 mM; calcium chloride 220-280 mM; the balance is water;

[0007] First, apply stimulating liquid to the surface of desert soil at a rate of 1.5 to 2.5 L / m 2 ;as well as

[0008] At least 24 hours later, apply cementing liquid to the surface of the desert soil, with an application rate of 1.5-2.5L / m 2 .

[0009] According to the method of the present invention, applying the stimulating liquid to the desert soil surface layer may include spraying the stimulating liquid multiple times, such as 4 times, with at least 24 hours between each spraying. Applying the cementing liquid to the desert soil surface layer may also include spraying the cementing liquid multiple times, such as 4 times, with at least 24 hours between each application.

[0010] According to the method of the present invention, the pH of the stimulation solution is preferably 7.1 to 7.5, more preferably about 7.3.

[0011] According to the method of the present invention, the pH of the binder solution is preferably 8.2 to 8.6, more preferably about 8.4.

[0012] According to the method of the present invention, the stimulation solution preferably comprises: 0.1 g / L yeast extract; 12.5 mM ammonium chloride; 42.5 mM sodium acetate; and 350 mM urea.

[0013] According to the method of the present invention, the binding liquid preferably comprises: 0.1 g / L yeast extract; 12.5 mM ammonium chloride; 42.5 mM sodium acetate; 350 mM urea; and 250 mM calcium chloride.

[0014] According to the method of the present invention, the amount of stimulating liquid sprayed each time is preferably 2L / m 2 The amount of adhesive sprayed each time is preferably 2L / m 2 .

[0015] According to the method of the present invention, the desert soil surface layer can be a conical sand dune or a trapezoidal sand dune surface layer. The method of the present invention is particularly suitable for the western edge of the Taklimakan Desert in Xinjiang Uygur Autonomous Region, China.

[0016] The present invention combines specific biological stimulation with cementation means to form a crust on the surface of desert soil, significantly improving the bearing capacity and wind erosion resistance of the surface of desert soil. In addition, the calcium content and strength of the desert soil are also increased.

[0017] The present invention adopts the biological stimulation method, the coagulation is relatively uniform, there is no mutual engulfment and competition between foreign bacteria and native bacteria, the transportation is safe, and there is no potential environmental pollution.

[0018] The present invention provides a reliable basis for implementing sand fixation and dust prevention strategies, alleviating sandstorms, and improving climate conditions in the Taklimakan region. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Test desert soil composition is shown.

[0020] Figure 2 The particle size distribution of the desert surface is shown.

[0021] Figure 3 Shown are the richness and diversity of desert soil bacterial communities.

[0022] Figure 4 The structural shape of the constructed conical dune is shown.

[0023] Figure 5a The structural shape of the constructed trapezoidal structured sand dune is shown; Figure 5b Its trapezoidal top view data is given.

[0024] Figure 6 A testing schedule is given.

[0025] Figure 7a , Figure 7b , Figure 7c The variation of bearing capacity over time for the D6 (0+1), D7 (1+1) and D8 (2+2) treatments is shown respectively.

[0026] Figure 8a , Figure 8b and Figure 8c The relationship between the crust thickness and time of the conical sand dunes under the D6, D7 and D8 treatments are shown respectively.

[0027] Figure 9a , Figure 9b and Fig.9c The relationship between wind erosion thickness and time of conical dunes under treatments D6, D7 and D8 are shown respectively.

[0028] Fig.10a , Fig.10b and Fig.10c The changes in bearing capacity over time under treatments T6, T7 and T8 are shown respectively.

[0029] Fig.11a , Fig.11b and Fig.11c The relationship between the crust thickness and time of the terraced sand dunes under the T6, T7 and T8 treatments is shown respectively.

[0030] Fig.12a , Figure 12b and Fig.12c The relationship between wind erosion thickness and time of the trapezoidal structure under treatments T6, T7, and T8 are shown respectively.

[0031] Fig.13 The relationship between the load-bearing capacity and the crust thickness including conical and trapezoidal structures is shown.

[0032] Fig.14a and Fig.14b SEM images of untreated and 1+1 treated samples, respectively.

[0033] Fig.15 is the micron area position when not treated; Fig.16 Its corresponding EDS image.

[0034] Fig.17 The micron area position for 1+1 processing; Fig.18 Its corresponding EDS image.

[0035] Fig.19 The micron area position for 2+2 processing; Fig. 20 Its corresponding EDS image. DETAILED DESCRIPTION

[0036] Prepare stimulation solution

[0037] The yeast extracts used in the present invention are all yeast extracts purchased from Nanjing Quanlong Biotechnology Co., Ltd.

[0038] Yeast extract 0.1g / L, ammonium chloride 12.5mM, sodium acetate 42.5mM, urea 350mM, the balance is deionized water. pH 7.3.

[0039] Prepare the cementing fluid

[0040] Yeast extract 0.1g / L, ammonium chloride 12.5mM, sodium acetate 42.5mM, urea 350mM, the balance is deionized water. pH 8.4.

[0041] Test site and sand analysis

[0042] The test site (77°22′49″E, 39°1′11″N) is located on the western edge of the Taklimakan Desert in Xinjiang Uygur Autonomous Region, China. The test site belongs to the continental arid, semi-arid and hyperarid climate zone, with an average annual rainfall of <38 mm and an average annual evapotranspiration of 3000 mm. The local ecological and geological environment is severely water-deficient and has strong evaporation characteristics. Rainfall mainly occurs from June to September. The temperature here varies greatly between day and night and between summer and winter, ranging from 67° in summer to -20° in winter. The average wind speed in the Taklimakan Desert varies between 3.5 and 10.9 m / s, with an average wind speed of 5.9 m / s. The test site is adjacent to the Kashi-Maigait Highway and is completely exposed to the natural environment, especially subject to severe erosion in spring. The wind here blows up the surface sand and deposits it elsewhere.

[0043] Desert soil is mainly composed of quartz. Figure 1 Its composition is shown; Figure 2 The particle size distribution of desert surface sand (0-10 cm) is shown; Figure 3 The richness and species of desert soil bacterial community are shown, where Proteobacteria dominate the community, accounting for 61%, followed by Bacteroidetes (13.57%) and Actinobacteria (11.38%). Table 1 lists the physical and hydrophysical properties of desert soil, which belongs to poorly graded sand in the Unified Soil Classification System (ASTM D2487-17).

[0044] Table 1

[0045]

[0046] Constructing a test dune model

[0047] (i) Construct a conical sand dune, the structure is as follows Figure 4As shown. 11 groups (3 groups in each group) of artificial sand dunes (D1-D11) were artificially formed using nearby surface sand. The dunes are 100 cm apart, about 40 cm high, about 120 cm in diameter at the bottom, with a dry density of about 1.48 g / cm3 and a natural angle of repose of about 34°. Conical sand dunes are used to simulate the wind erosion of sand dunes in the desert, in which a total of 5 wind erosion needles are arranged, one inserted into the top of the cone and the other 4 inserted in the middle of the slope. Each wind erosion needle is inserted vertically into the base and protrudes (exposed to the surface) by 100 mm. The wind erosion length is the average of the 5 wind erosion needles. The wind erosion part is equal to the protruding length measured each time minus 100 mm.

[0048] (ii) Constructing trapezoidal sand dunes, such as Figure 5a As shown, Figure 5b The data of the top view of the trapezoid are given. A wooden trapezoidal frame is used for construction, and there is no cover on the top and bottom. The upper side is 1m long, the lower side is 1.3m long, the height is 10cm, and the inclination angle between the side and the bottom is 34 degrees, which is exactly equal to the repose angle of desert soil. The specific process is: the trapezoidal wooden mold is gently placed on the ground, and 21.36 kg of desert soil (the internal volume of the trapezoidal mold is 14433cm 3 The dry density of sand is 1.48 g / cm 3 ). At a distance of 10cm from the upper surface of the trapezoid, the desert soil was slowly poured into the mold. After pouring, it was gently and evenly leveled with a soil scraper. Finally, the mold was removed to form a trapezoidal dune to simulate the wind erosion of flat desert soil. The trapezoidal desert soil structure also has 5 wind erosion needles, and the wind erosion length is also taken as the average of the 5. Like the conical dunes, the trapezoidal dunes are also divided into 11 groups (T1-T11), and three replicates are set in each group to reduce accidental errors.

[0049] Sand dune treatment solutions

[0050] The treatment scheme is shown in Table 2. "D" represents a conical sand structure and "T" represents a trapezoidal sand structure. D1 and T1 were not treated. D2-D6 and T2-T6 were sprayed once and measured 0, 1, 4, 7, 14, and 28 days after each treatment. D7 (1S+1C, or 1+1 for short) represents a treatment: first spray 2L / m 2 of irritant solution, and then spray 2L / m after 24 hours 2 Cementing fluid. Tests were conducted 0, 1, 4, 7, 14, and 28 days after the treatment. Here, day 0 means that the test started immediately after the last spraying. D8(2S+2C), sometimes abbreviated as D8(2+2) or simply 2+2, represents the treatment: first spray the irritant, then spray the irritant again 24 hours later, then spray the cementing fluid 24 hours later, and then spray the cementing fluid again 24 hours later, all of which were sprayed at 2 L / m 2The spraying interval is always 24 hours, which can also be expressed as (S+S+C+C). D9, D10, D11, etc. follow a similar pattern. Similarly, T1-T11 follow a similar pattern, but aim for a trapezoidal structure.

[0051] Table 2

[0052]

[0053]

[0054] Processing performance test

[0055] The test time starts after each treatment is completed. The test schedule is as follows Figure 6 For convenience, Figure 6 In the figure, the vertical axis type I represents the situation D1-D6 or T1-T6; II represents D7 or T7; III represents D8 or T8; IV represents D9 or T9; V represents D10 or T10; VI represents D11 or T11.

[0056] The bearing capacity of the samples was measured using a micro penetrometer. The crust thickness and erosion thickness were measured using a vernier caliper. In order to analyze the microscopic changes in the internal structure of the desert soil before and after solidification by biostimulation method in the field test, selected samples were subjected to microscopic analysis using SEM (scanning electron microscope, Regulus 8100, Hitachi, Japan) and EDS (energy dispersive spectroscopy, Bruker, QUANTAX).

[0057] Changes of bearing capacity B with time under treatments D1-D11

[0058] Under the treatments D1-D11, the bearing capacity gradually increased from 0 kPa without treatment to nearly 280 kPa for the treatment of D11. For the treatments D1-D5, the bearing capacity also gradually increased, and their approximate relationship was BD5>BD4>BD3>BD2>BD1. Due to their relatively small strength, less than 30 kPa, they were blown away by natural wind before the 7th day and could not resist the erosion of the natural sandstorm in the Taklimakan Desert. The maximum wind speed in this area was about 9 m / s. The treatments D6, D7, D8, D9, D10, and D11 were not blown away under natural conditions, indicating that they all have the potential to solidify the desert soil layer and prevent dust under natural wind conditions. The relationship between their maximum strengths is roughly as follows: BD11 (280 kPa) > BD10 (270 kPa) > BD9 (250 kPa) > BD8 (195 kPa) > BD7 (140 kPa) > BD6 (70 kPa). Considering the impact of treatment cost and time, D6, D7, or D8 are most suitable for practical application. Although D9, D10, and D11 can achieve greater bearing capacity and thus greater resistance to wind erosion, the increase is not decisive compared to D7 or D8, and the additional strength may not be required to consolidate sand and prevent dust. Figure 7a , Figure 7b , Figure 7c The bearing capacity of D6 (0+1), D7 (1+1) and D8 (2+2) treatments over time are shown respectively: on the 7th day, the bearing capacity of D6 has reached 70 kPa, the bearing capacity of D7 is about 130 kPa, and the bearing capacity of D8 is 200 kPa. After 28 days, it remains basically unchanged. Considering economic, time and safety factors, the (1+1) treatment, i.e. D7, can be preferred.

[0059] Changes of crust thickness C over time under treatments D1-D11

[0060] The crust thickness usually increases from D1 (0 mm) to D11 (10 mm). Figure 8a , Figure 8b and Figure 8c The relationship between the crust thickness and time of the conical sand dunes under the D6, D7 and D8 treatments is shown respectively. The crust thickness of the D6 treatment is significantly lower than that of D7 and D8. However, there is a slight increase from D7 to D8, but not much. Overall, CD8 (6mm)>CD7 (5mm)>CD6 (2mm). The crust thickness of CD6 is only about 2 mm, which may be beneficial to plant growth. Since D1-D5 was blown away by the sandstorm during the solidification period, there is no available data. The study of crust thickness provides a basis for future research on the compatibility of plants and microbial sand fixation, because thicker crusts may hinder plant growth. Changes in erosion thickness W over time under treatments D1-D11

[0061] The erosion thickness generally decreases from D1 (240 mm) to D11 (5 mm), and most of the erosion occurs on the first day. After the first day, the erosion thickness generally remains relatively constant because the strength of the treated desert soil can resist wind erosion, indicating that the sandstorm can no longer erode the sand surface. Figure 9a 、 Figure 9b and Fig.9c respectively show the relationship between the wind erosion thickness and time of conical sand dunes under D6, D7 and D8 treatments. The erosion thickness of the D6 (25 mm) treatment is significantly higher than that of the D7 (12 mm) and D8 (11 mm) treatments. However, there is little difference between D8 and D7. Generally speaking, WD8 < WD7 < WD6. The study of wind erosion thickness is of great significance for the compatibility of plant and microbial sand fixation and future engineering construction. The change of bearing capacity B with time under T1-T11 treatments

[0062] Under the T1-T11 treatments, the bearing capacity gradually increases from almost 0 kPa when untreated to a maximum of 300 kPa in the D9 (4 + 4) treatment. Under the T1 (0 kPa)-T5 (30 kPa) treatments, the bearing capacity also gradually increases, and the general relationship is BT5 > BT4 > BT3 > BT2 > BT1. Due to their relatively small strength, under natural erosion conditions, they were blown away by the sandstorm within seven days and could not resist the erosion of the natural sandstorm in the Taklimakan Desert. The maximum wind speed in this area is about 9 m / s. T6, T7, T8, T9, T10, T11 were not blown away under natural conditions, indicating that they all have the potential to solidify sand and prevent dust under natural sandstorm conditions. The bearing capacity reaches the maximum value during the T9 treatment, and gradually decreases during the T10 and T11 treatments. The relationship of their maximum strength is roughly as follows: BT9 (300 kPa > BT10 (260 kPa) > BT11 (250 kPa) > BT8 (245 kPa) > BT7 (165 kPa) > BT6 (90 kPa). Considering the influence of treatment cost and time, T6, T7 or T8 may be the most suitable for practical applications. Although T9, T10, T11 can achieve greater bearing capacity and thus have stronger wind erosion resistance, compared with T7 or T8, the increase is not significant, and only for solidifying sand and preventing dust, additional strength may not be required. Fig.10a 、 Fig.10b and Fig.10c respectively show the change of bearing capacity with time under T6, T7 and T8 treatments. The bearing capacity of T6 reaches 80 kPa on the 7th day, the bearing capacity of T7 is about 150 kPa, and the bearing capacity of T8 reaches 220 kPa on the 7th day and hardly changes after 28 d. Considering economy, time and safety, the T7 (1 + 1) treatment, that is, T7, can be selected as a potential optimal solution. Incidentally, for the maximum bearing capacity, the trapezoidal structure seems to be superior to the conical structure.

[0063] Changes of crust thickness C over time under treatments T1-T11

[0064] The maximum crust thickness usually increases from T1 (0 mm) to T11 (13 mm), and the thickest part is at T11, close to 13 mm. Fig.11a , Fig.11b and Fig.11c The relationship between crust thickness and time for the terraced dunes under treatments T6, T7, and T8 is shown. Overall, the order of maximum crust thickness is CT8 (7 mm) > CT7 (5 mm) > CT6 (3 mm). The crust thickness of the terraced structures is generally thicker than that of the conical structures. Changes in erosion thickness W over time under treatments T1-T11

[0065] The maximum wind erosion thickness generally decreased from T1 (100 mm) to T11 (2 mm). For the T1-T5 treatments, erosion occurred mainly within the first 4 days and remained relatively constant thereafter. By the 7th day, the T1-T5 treatments were almost completely eroded, which may be directly related to the lack of cementing material and limited strength. In contrast, the erosion thickness of T7-T11 was very small, approximately 2 mm, which may be due to the complete solidification of the desert surface and the inability of the maximum wind force in the desert environment to move the sand. Fig.12a , Figure 12b and Fig.12c The relationship between wind erosion thickness and time of the trapezoidal structure under treatments T6, T7, and T8 is shown respectively. Overall, there is almost no difference in their erosion thickness.

[0066] Relationship between bearing capacity and crust thickness

[0067] For the D1-D5 and T1-T5 treatments, they were completely blown away by local dust storms after the 4th day. Fig.13 The relationship between the bearing capacity and the crust thickness, including conical and trapezoidal structures, is shown. It can be seen from the figure that for the 0+1, 1+1, and 2+2 treatments (S10f-h, S11f-h), the bearing capacity increases faster with the increase in thickness, and the slope of the regression line is relatively large. For the 4+4, 6+6, and 8+8 treatments, the bearing capacity increases more slowly with the increase in thickness, and the slope of the regression line is relatively small. It can also be seen from the figure that when the desert soil is stabilized using biostimulation, the crust thickness is positively correlated with the bearing capacity. This can provide reliable data for future microbial solidification, plant compatibility, and engineering applications of sand.

[0068] Microstructure analysis

[0069] Fig.14a and Fig.14bThe SEM images of the untreated and 1+1 treated samples are shown in the figure. As shown in the figure, the microstructure of the untreated sample has a smooth surface, sharp edges and corners, and no filling in the pores; while the 1+1 treated sample has cement on the surface and filling in the pores. According to the cementation mechanism, the filling should be calcite crystals, such as Fig.14b Shown in the red box.

[0070] Fig.15 is the micron area position when not treated, Fig.16 Its corresponding EDS image. Fig.17 The micron area position for 1+1 processing, Fig.18 Its corresponding EDS image. Fig.19 The micron area position for 2+2 processing, Fig. 20 The corresponding EDS image is shown in the figure. As can be seen from the figure, the Ca content in the untreated sample is zero, while the Ca content in the 1+1 treatment is 5.38%, and the Ca content in the 2+2 treatment is 7.56%. The gradual increase in the Ca content also indicates that the cementation effect is getting better and better. This also explains the gradual increase in its strength.

[0071] The biostimulation method used in the present invention is carried out under completely natural conditions in the wild. It is a brand-new attempt and is carried out under conditions that are completely uncontrolled by humans. The two desert soil structures are used entirely to simulate the natural slope of the desert site, because the desert is not flat. In the experiment, the difference between the conical structure and the trapezoidal structure may be related to the penetration angle and penetration path of the spraying liquid. Under the same conditions, the effect of the trapezoidal structure is better than that of the conical structure.

[0072] For the cases of untreated D1, deionized water D2, mineral water D3, tap water D4, and pure stimulating liquid D5 (1+0), although the consolidation effect gradually improves, under natural conditions in the field, the crust thickness is too thin and has been destroyed during the maintenance stage. The erosion thickness reaches the maximum and is not enough to achieve the purpose of sand fixation. Pure water is almost the same as mineral water. After being dried by the wind, it is the same as untreated water. Tap water may contain many impurities and some bacteria, which slightly increase the consolidation effect. Pure stimulating liquid may contain a small amount of hydration to produce carbonate ions, which combine with a small amount of calcium ions in the desert to form calcium carbonate, so its strength increases, but it is still not enough to resist erosion under field conditions.

[0073] For the case of D6 (0+1) with only the cementing liquid, the strength is significantly increased because the cementing liquid itself contains the irritant liquid and the cementing liquid. The difference between D6 and D7 (1+1) is that in the D7 treatment, the irritant liquid is sprayed 24 hours later, and the cementing liquid (calcium ions) are added after the urea is fully hydrolyzed to generate enough carbonate ions, so that the solidification is more solid. Although the cementing liquid in the D6 treatment also contains the irritant liquid and the cementing liquid, the strength is not as good as that of the D7 treatment, probably because the irritant liquid does not have enough time to activate the bacteria in the soil and hydrolyze the urea, and the carbonate ions generated are limited. However, since D6 generates enough crust thickness to resist wind erosion in the field, the wind erosion thickness remains basically unchanged after the 4th day.

[0074] The reason why D8 (2+2) and D9 (4+4) used multiple spraying of stimulating liquid was to fully activate the urea-hydrolyzing bacteria in the soil, making them fully activated, fully hydrolyzing urea, and producing the maximum amount of carbonate ions to fully combine with calcium ions to form calcium carbonate. As the number of spraying increased, the solidification effect became better and better. By the time of D9 treatment, the effect was good, that is, the bearing capacity was the highest, the crust thickness was the largest, and the wind erosion thickness was the smallest.

[0075] The results show that the curing effects of D10 (6+6) and D11 (8+8) are not much different from those of D9, or even slightly lower than those of D9. The reason may be that the organic matter and calcium carbonate produced by excessive spraying blocked the pores of the shallow particles of the desert soil, making it impossible for the solution sprayed later to enter the soil evenly. It may also be that the carbonate ions produced in the cementing solution sprayed later partially dissolved the generated calcium carbonate, resulting in a decrease in strength. This shows that the more spraying times, the better the effect. However, due to the large number of spraying times, the crust thickness will increase, and the erosion thickness will remain basically unchanged after the fourth day.

[0076] Regarding the curing effect, although D9>D8>D7>D6, considering the cost and time factors, D7(1+1) treatment is recommended in actual use.

[0077] For the trapezoidal structure (T1-T11), the situation is basically similar. As for the curing time, most of the curing is generally completed in the first 7 days. After 14 days, the strength has only changed slightly, indicating that the curing has been basically stable. After more than 30 days, due to the erosion of wind and sand in the field, the strength of some samples has decreased, and the thickness of the crust has also decreased. For the field curing of desert soil by biostimulation, the relationship between strength and crust thickness was regressed for different sand structures and different treatments: as the number of spraying increases, the regression slope decreases, which also shows that the curing effect does not increase linearly with the number of spraying, but a passivation phenomenon occurs. But in general, there is a positive correlation between bearing capacity and crust thickness.

[0078] Microscopic tests have proven that calcite crystals are indeed generated inside the desert soil, and generally speaking, the calcite content increases with the number of sprayings. This once again proves the correctness and feasibility of the field soil solidification mechanism of biostimulation. Figure 3 As shown, in the Taklimakan Desert soil, three bacteria Proteobacteria, Bacteroidetes, Actinobacteria accounted for 60.99%, 13.57%, and 11.38% respectively. The experimental results show that the stimulating solution (nutrient solution) used is effective for the desert soil dominated by the above microorganisms.

[0079] The present invention provides a reliable guarantee for the large-scale implementation of sand fixation and dust prevention in the Kashgar area in the future, preventing frequent sandstorms and improving local climate conditions and the sanitary conditions of residents.

Claims

1. A method for biostimulation of sand fixation and dust prevention for the surface layer of desert soil, comprising: Prepare a stimulation solution, the composition of which is: yeast extract 0.08-0.12 g / L; Ammonium chloride 11-14 mM; sodium acetate 40-45 mM; urea 300-400 mM; the balance is water; Prepare a binder solution, the composition of which is: yeast extract 0.08-0.12 g / L; ammonium chloride 11-14 mM; sodium acetate 40-45 mM; urea 300-400 mM; calcium chloride 220-280 mM; the balance is water; First, apply stimulating liquid to the surface of desert soil at a rate of 1.5 to 2.5 L / m 2 ; as well as At least 24 hours later, apply cementing liquid to the surface of the desert soil, with an application rate of 1.5-2.5L / m 2 .

2. The method according to claim 1, wherein applying the stimulating liquid to the surface layer of desert soil comprises spraying the stimulating liquid multiple times, with each spraying being at least 24 hours apart.

3. The method according to claim 1, wherein applying the binder to the surface layer of the desert soil comprises spraying the binder multiple times, with each spraying being at least 24 hours apart.

4. The method according to claim 1, wherein the pH of the stimulation solution is 7.1 to 7.

5.

5. The method according to claim 1, wherein the pH of the binder is 8.2 to 8.

6.

6. The method according to claim 1, wherein the desert soil surface layer is a conical sand dune or a trapezoidal structure sand dune surface layer.

7. The method according to claim 6, wherein the desert is located in the western edge of the Taklimakan Desert in Xinjiang Uygur Autonomous Region, China.